Investigation of the Single-Point Diamond Turning of Optics-Grade Germanium Substrate - Kesme, Kamer Dorukhan; Aydın, Tahsin; Yartaşı, Ekrem (Fırat University, 2026)
This study investigates the influence of cutting parameters on surface roughness (Sa) in diamond turning of optical-grade single-crystal germanium lenses. Specimens (Ø40 mm, 2 mm thick) were machined on an ultraprecision single-point diamond turning (SPDT) lathe; surfaces were characterized using Fizeau and white-light interferometers, accompanied by surface topography maps. Experiments followed a 3×2×2 factorial design (V: 1000–3000 rpm; d: 3–6 ?m; fr: 2–5 mm/min) with constant tool geometry (rake ? = ?25°, clearance ? = 10°). The best Sa achieved was 1.065 nm, well below the accepted 4.640 nm threshold. From the measurements, two predictive models—linear and nonlinear—were established to relate Sa to the process parameters. The design enabled rapid exploration of settings and interactions (V–d–fr). The models provide practical tuning windows and sensitivity guidance to reach the 1–3 nm target band. Overall, the study offers a deployable framework for in-process optimization.

Bu çalışma, optik kalite tek kristal germanyum lenslerin tornalanmasında kesme parametrelerinin yüzey pürüzlülüğü (Sa) üzerindeki etkisini incelemektedir. 40 mm çap, 2 mm kalınlıktaki numuneler ultra hassas tek nokta elmas tornalamada işlenmiş, yüzeyler Fizeau ve beyaz ışık interferometreleriyle karakterize edilmiştir. Sa değerlerine eşlik eden topografik yükseklik haritaları türetilmiştir. Deneyler, 3×2×2 faktöriyel tasarım altında yürütülmüştür (V: 1000–3000 rpm; d: 3–6 µm; fr: 2–5 mm/dk). Takım geometrisi sabit tutulmuştur (talaş açısı ?=?25°, boşluk açısı ?=10°). En iyi Sa değeri 1.065 nm olarak elde edilmiş ve bu değer kabul edilen 4.640 nm sınırının belirgin biçimde altındadır. Ölçümlerden elde edilen veri setiyle, Sa’yı parametrelerle ilişkilendiren lineer ve lineer olmayan iki tahmin modeli kurulmuştur. Tasarım, üretim ayarlarının hızlı taranmasına ve etkileşimlerin (V–d–fr) anlaşılmasına olanak vermiştir. Modeller, 1–3 nm hedef aralığına inmek için pratik ayar pencereleri ve duyarlılık bilgisi sağlamaktadır. Çalışma, yerinde proses optimizasyonu için uygulanabilir bir çerçeve sunar.
Optik Kalite Germanyum Alttaşın Tek Nokta Kristal Elmas ile Tornalanmasının İncelenmesi
Keywords: Electronic; Optics and Magnetic Materials; Elektronik; Optik ve Manyetik Malzemeler; Machining; Makine İle İşleme